PENGARUH STRATEGI MARKETING COMMUNICATION TERHADAP KEPUASAN PELANGGAN SHOPEE FOOD DI SIDOARJO - Akmal, Ichsanuddin; Setianingrum, Vinda Maya (The Commercium, 2024)
Online shopping activities have now become a trend in society. One of the marketplace applications that is currently being used is the Shopee application. Shopee is not only engaged in e-commerce, but also develops business in the food sector or commonly called "Shopee Food". This feature is one of Shopee's development efforts in accommodating convenience for its consumers in purchasing food or drinks online. This study aims to determine how much influence Marketing Communication has on Shopee Food customer satisfaction in Sidoarjo. This research is quantitative research with a cross sectional approach. The data used are primary data and secondary data collected through observation, distributing questionnaires, and documentation. The population used was Shopee Food customers in Sidoarjo with a sample of 96 respondents who were taken using accidental sampling technique. The validity test and reliability test were used to test the validity of the data in this study. Furthermore, the data were analyzed using a simple linear regression test. The results showed that marketing communication strategy affects Shopee food customer satisfaction in Sidoarjo with a percentage of 32.6%. The remaining 67.4% (100%-32.6%) is caused by other factors, namely product quality, service quality, and pricing. Partial and simultaneous test results show that marketing communication strategies affect Shopee food customer satisfaction in Sidoarjo. This research is expected to be utilized to improve marketing communication strategies in order to make customers satisfied, as well as a reference for improvement for further research.